PEMBERDAYAAN PEREMPUAN DALAM PENGUATAN KEWIRAUSAHAAN KELUARGA BERBASIS UMKM DI DESA JATIBARU KECAMATAN CIASEM - KABUPATEN SUBANG - Shinta Aulia; Abdurohim (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the role of women's empowerment in strengthening family-based Small and Medium Enterprises (SMEs) in Jatibaru Village, Ciasem District, Subang Regency. Women's empowerment in this village includes various initiatives such as skills training, market access, and provision of business capital that support the management of SMEs by women. The results show that women's empowerment significantly contributes to improving the performance and sustainability of family-based SMEs, as well as strengthening family and village economic resilience. However, challenges such as limited access to capital, education, and technology remain obstacles that need to be addressed. Based on these findings, it is recommended to strengthen policies for empowering women by providing easier access to capital, more structured training, and technological support to enhance the competitiveness of women-led SMEs in the village.